2015
DOI: 10.1016/j.geomorph.2015.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Palaeo-ice stream pathways and retreat style in the easternmost Amundsen Sea Embayment, West Antarctica, revealed by combined multibeam bathymetric and seismic data

Abstract: Multibeam swath bathymetry data sets collected over the past two decades have been compiled to identify palaeo-ice stream pathways in the easternmost Amundsen Sea Embayment. We mapped~3000 glacial landforms to reconstruct ice flow in the~250-km-long cross-shelf Abbot Trough. This bathymetric feature was occupied by a large ice stream, which was fed by two tributaries (Cosgrove and Abbot) and reached the continental shelf edge during the last maximum ice sheet advance. Geomorphological mapping has enabled a cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 70 publications
(100 reference statements)
3
38
0
Order By: Relevance
“…However, a flattening in trough profile beyond the mid-shelf and the existence of multiple outer-shelf troughs, including new landform evidence of streaming ice within Abbot Trough ( Fig. 1b; Klages et al 2015), raises the possibility that outer parts of the ice sheet were configured in widespread distributed fast ice flow or even as divergent fast-flowing trunks during glacial maxima ). Although we cannot constrain the precise glaciological regime, it is evident from recent mapping that the geomorphological character of the outer shelf is as complex as the inner-shelf counterpart, and not a relatively simple imprint of full-glacial conditions (cf.…”
Section: Discussion: Landform Distribution and Schematic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a flattening in trough profile beyond the mid-shelf and the existence of multiple outer-shelf troughs, including new landform evidence of streaming ice within Abbot Trough ( Fig. 1b; Klages et al 2015), raises the possibility that outer parts of the ice sheet were configured in widespread distributed fast ice flow or even as divergent fast-flowing trunks during glacial maxima ). Although we cannot constrain the precise glaciological regime, it is evident from recent mapping that the geomorphological character of the outer shelf is as complex as the inner-shelf counterpart, and not a relatively simple imprint of full-glacial conditions (cf.…”
Section: Discussion: Landform Distribution and Schematic Modelmentioning
confidence: 99%
“…GZW1 is c. 15 m thick, while GZW 2 may be .40 m high. Equivalent and probably corresponding wedges are also mapped to the east in Abbot Trough (not shown; Klages et al 2015).…”
Section: Outer-shelf Trough and Upper Continental Slopementioning
confidence: 99%
“…Multibeam‐swath bathymetry data revealed that several bathymetric troughs extend from the modern ASE coast across the continental shelf to near the shelf break [e.g., Nitsche et al ., ; Jacobs et al ., ; Livingstone et al ., ; Larter et al ., ] (see Figure ). A variety of subglacial bedforms mapped within these troughs give evidence that the troughs mark the pathways of fast‐flowing paleo‐ice streams, which had advanced across the ASE shelf during past glacial periods [ Lowe and Anderson , ; Evans et al ., ; Graham et al ., , ; Larter et al ., ; Jakobsson et al ., , ; Nitsche et al ., ; Klages et al ., , ]. In contrast, a distinct bed form assemblage observed on an intervening shallow ridge suggests that paleo‐ice flow there was slower than in the neighboring troughs [ Klages et al ., ].…”
Section: Glaciological Changes In the Asementioning
confidence: 99%
“…Small repeating corrugation ridges have been observed within fields of iceberg furrows or within individual iceberg furrows (Fig. 2h, k;Anderson, 1999;Jakobsson et al, 2011;Klages et al, 2015). Although the exact mechanism for their formation remains somewhat controversial, corrugation ridges are thought to form as icebergs move vertically with tides, causing iceberg keels to intermittently contact the bed (Jakobsson et al, 2011;Graham et al, 2013).…”
Section: Ice-marginal Featuresmentioning
confidence: 99%